HUBUNGAN TINGKAT PENGETAHUAN DENGAN SELF CARE MANAGEMENT PADA PENDERITA HIPERTENSI DI RW 05 KELURAHAN BOJONGSARI KOTA DEPOK TAHUN 2023 - Shifa Muhibah; Hutasoit, Mey Lys Ceryah; Suzanna Fabella Putri (Jurnal Kesehatan STIKes IMC Bintaro, 2024)
Background: Hypertension is a condition of systole blood pressure of more than 140 mmHg and diastole above 80 mmHg. Hypertension can be controlled by doing self care management to control factors that affect blood pressure. Good self care management is influenced by several factors, one of which is knowledge. Research Objective: To determine the relationship between the level of knowledge and self care management in hypertension patients at RW 05 Bojongsari Village, Depok City. Research Methodology: Using observational quantitative research design with a Cross Sectional approach. The sample in the study was 40 respondents with simple random sampling techniques. Research Results: Based on the results of the chi-square alternative test, namely the Fisher's Exact test, the results of the majority of respondents who are hypertensive patients have a good level of knowledge with good self care management behavior (64,0%). Relationship analysis using the Fisher's Exact test obtained a significant value p value = 0.003 (<0.05), then the hypothesis in this study was accepted and H0 was rejected, and OR (CI: 95%) was obtained 11,556 (2,115-63,127). Conclusion: There is a relationship between the level of knowledge and self care management in people with hypertension in RW 05 Bojongsari Village, Depok City. It is concluded that the better a person's knowledge, the better the self care management will be.